Disfungsi Penggunaan Aplikasi Media Sosial Dalam Pendidikan Agama Kristen Keluarga di Desa Pusian Selatan, Kecamatan Dumoga, Kabupaten Bolaang Mongondow - Hasia Mamonto; Ellen S. Kambey; Semuel Selanno (Peneliti.net, 2022)
The purpose of this study, namely to obtain the results of analysis and description of data about the use of social media applications that have an impact on Family Christian Religious Education by mothers in Pusian Selatan Village, the factors causing social media applications are not used according to their functions in Family Christian Religious Education by mothers. -mothers in South Pusian Village and efforts to overcome the causes of the use of social media applications that are not in accordance with their functions in Family Christian Religious Education by mothers in South Pusian Village. To achieve the research objectives, the researchers used a qualitative approach with analytical descriptive methods by following the design of Miles and Huberman in data collection, namely observation, interviews and document studies, then the data obtained were analyzed through analytical procedures with several stages, namely reduction, display, and drawing conclusions /verification. Based on the results of the study, the researchers concluded that (1) there was a dysfunction in the use of social media applications in Family Christian Religious Education (2) the causal factor was due to a lack of self-control towards feelings of lack of digital literacy and considerations about the good and bad in the use of social media related to cyber ethics because lack of teaching or coaching from the church and government, (3) The efforts made are efforts from family members, government and church.